The Copyright Surveillance Industry - Zajko, Mike (2015)
Creative works are now increasingly distributed as digital “content” through the internet, and copyright law has created powerful incentives to monitor and control these flows. This paper analyzes the surveillance industry that has emerged as a result. Copyright surveillance systems identify copyright infringement online and identify persons to hold responsible for infringing acts. These practices have raised fundamental questions about the nature of identification and attribution on the internet, as well as the increasing use of algorithms to make legal distinctions. New technologies have threatened the profits of some media industries through copyright infringement, but also enabled profitable forms of mass copyright surveillance and enforcement. Rather than a system of perfect control, copyright enforcement continues to be selective and uneven, but its broad reach results in systemic harm and provides opportunities for exploitation. It is only by scrutinizing copyright surveillance practices and copyright enforcement measures that we can evaluate these consequences.